Metaphorical discourse in Beijing Winter Olympic news: a Trinocular Perspective analysis of language, cognition, and social functions - Peng, Wei; Li, Qingping (Frontiers in Psychology, 2024)
This study utilizes the “Trinocular Perspective” metaphor analysis framework to delve into the language, cognition, and social functions of metaphors in news coverage of the Beijing Winter Olympics and their interactions, thereby revealing the role of metaphors in shaping and articulating the narratives within Olympic news communication. The research indicated that, at the linguistic level, metaphors enhanced the expressiveness and appeal of news discourse through diverse forms and dense distribution. At the cognitive level, metaphors fostered a deeper public understanding of abstract concepts such as the Olympic spirit, the values of a community with a shared future for mankind, China’s national image, and the concept of sustainable development. On the social function level, metaphors will play a pivotal role in building social identity, disseminating values, highlighting social issues, and promoting social change. The language, cognition, and social functions of metaphors were closely interwoven, with linguistic expressions enriching cognitive frameworks, cognitive frameworks guiding the internalization and dissemination of social values, and social functions guiding public cognition through the strategic use of metaphorical language. This study reveals the critical function of metaphors in elevating the narrative richness and dissemination efficacy within the journalism of large-scale international sports competitions.